Assessment of ultraviolet‐radiation‐induced DNA damage within melanocytes in skin of different constitutive pigmentation. (2nd April 2013) - Del Bino, S.; Sok, J.; Bernerd, F.
Summary Background Melanoma incidence and pigmentary disorders are known to be related to the degree of skin pigmentation, but few data exist on the specific impact of ultraviolet radiation (UVR) on melanocytes in skin of different constitutive pigmentation. Objectives To analyse UVR‐induced DNA damage within melanocytes in different skin‐colour types. Methods Skin samples were objectively classified into light, intermediate, tan, brown and dark skin according to their individual typology angle (°ITA), based on colorimetric parameters. Samples were exposed to increasing doses of solar simulated radiation. Detection of DNA damage specifically in melanocytes was achieved by cyclobutane thymine dimer (CPD)–tyrosinase‐related protein 1 double staining. Results For light, intermediate and tan skin, accumulation of CPDs in melanocytes was detected at the lowest dose, with a steep increase with dose. At estimated erythemally equivalent doses, around 80–100% of melanocytes were positive for CPDs in tan, intermediate and light skin types. In contrast, in dark and brown skin types, CPDs were found in only approximately 15% of melanocytes at the highest dose. Conclusions This work demonstrates that melanocytes from constitutively highly pigmented skin types are less impacted in terms of UVR‐induced DNA damage than those from lighter skin types, even those that are moderately pigmented.